Ekonomiczne aspekty secesji. Uwagi na temat gospodarczych efektów secesji w koncepcji Hansa-Hermanna Hoppego - Hankus, Przemysław Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The paper examines Hans-Hermann Hoppe’s economic rationale for secession and arguments presented in the works of this thinker in favor of secession. After a brief introduction to his views on the issue in question main drawbacks in his argumentation are being pointed out, conclusions are being drawn and suggestions are being made as to what and where should be changed and fixed in order to make it no longer suffering from inconsistencies and methodological slips as well as presenting more coherent set of claims
Keywords: secesja; decentralizacja; Hoppe, Hans-Hermann (1949- ); libertarianizm; szkoła austriacka